Pojęcie kontroli w prawie dotyczącym pomocy Unii Europejskiej dla rolnictwa - STANIEWSKA, ANNA (Wydawnictwo Naukowe UAM, 2010)
Control is one of the key elements in all support systems offered by the European Union. Special tools and control procedures are found in the Common Agricultural Policy (CAP). Control within the EU support for agriculture functions based on a specific system, referred to as the integrated administration and control system. In the conclusion the Author stated that the concept of control found within the EU support system for agriculture is not equivalent to the concept of control existing in the Polish doctrine of administrative law, in which control is defined in opposition to supervision, as a process devoid of authority elements. In contrast, the analysed concept is closer to the definitions originating from the Anglo-Saxon legal tradition, according to which control is a process of management and regulation. The Author proposed the following definition of the analysed concept: it is a cyclical regulation process, initiated by a comparison of the analysed object to a model, of legal or actual character, in the course of which obtained information is used both to modify the legal situation of the controlled subject and the actual situation of the implemented control system.

Il controllo è uno degli elementi chiave di tutti i sistemi di sostegno offerti dall’Unione Europea. La politica agricola comune (PAC) prevede degli strumenti e procedure speciali. Il controllo nell’ambito del sostegno all’agricoltura funziona in base al sistema speciale denominato sistema integrato di gestione e controllo. In conclusione l’Autrice afferma che la nozione di controllo impiegata dalla PAC non equivale a quella utilizzata dal diritto amministrativo, secondo la dottrina in quest’ambito il controllo è definito in opposizione alla sorveglianza, come un processo privato di elementi autoritari. La nozione analizzata è più vicina alle definizioni di tradizione giuridica anglosassone, secondo le quali infatti il controllo è un processo di carattere gestionale e regolativo. L’Autrice propone la seguente definizione della nozione analizzata; secondo la stessa il controllo è un processo ciclico regolativo che inizia ponendo a confronto l’oggetto analizzato con il modello, di carattere giuridico o reale. Seguendo il processo si ottengono informazioni che possono essere utilizzate sia per costruire la situazione giuridica del soggetto controllato, sia per definire la situazione effettiva del sistema di controllo implementato.